Puerto Rican collection - Puerto Rico.; Coll y Toste, Cayetano, 1850-1930.
Chiefly documents of the Spanish colonial government in Puerto Rico including orders and decrees, military records of the Spanish Ministerio de la Guerra, and financial records pertaining to budgets, imports and exports, and taxation. Also includes baptismal records; material concerning education (1898-1900), the fortification of "El Morro" in San Juan, political prisoners, politics, registration of foreigners, and slavery; and research materials of Puerto Rican historian and government official Cayetano Coll y Toste.
Microfilm edition of container 7 available
Microfilm edition of a register of foreigners (portion of container 8) and of a transfer of political prisoners (portion of container 10) available
Microfilm produced from originals in the Manuscript Division.
Collection material in Spanish, with English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Volumes concerning the budget and finance of Puerto Rico, pamphlets, and other records were formerly cataloged separately under Cayetano Coll y Toste collection relating to Puerto Rico, 1850-1894 (MSS80473).
Keywords: Spain. -- Ministerio de la Guerra -- History; Aliens -- Puerto Rico; Baptismal records -- Puerto Rico; Education -- Puerto Rico; Exports -- Puerto Rico; Finance, Public -- Puerto Rico; Fortification -- Puerto Rico; Imports -- Puerto Rico; Political prisoners -- Puerto Rico; Slavery -- Puerto Rico; Spanish-American War, 1898 -- Puerto Rico; Taxation -- Puerto Rico; Morro (San Juan, P.R.); Puerto Rico; Puerto Rico -- Commerce; Puerto Rico -- History -- To 1898.; Puerto Rico -- History, Military; Puerto Rico -- Politics and government -- To 1898.; Spain -- Colonies -- America